Community Empowerment Through the Utilization of Local Food-Based Pecotot Reborn MSMEs in Pulau Sejuk Village, Datuk Limapuluh District - Damanik, Rodhiatam Mardiah; Nainggolan, Elizon (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze community empowerment through the utilization of local food-based Pecotot Reborn MSMEs in Pulau Sejuk Village, Datuk Limapuluh District. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the management of Pecotot Reborn MSMEs reflects a collaborative empowerment pattern between the village government and business actors. The government still plays a primary role but provides participatory space in strategic decision-making. Community empowerment is reflected through six main indicators: authority, confidence and competence, trust, opportunities, responsibilities, and support. Pecotot Reborn MSMEs are able to improve digital promotion capabilities, maintain product quality, expand business networks, and innovate in local food development. Government support through training, capital, and promotion also strengthens business sustainability. Overall, Pecotot Reborn MSMEs contribute significantly to increasing income, economic independence, and preserving local food for the people of Pulau Sejuk Village.